A Multifaceted Takotsubo Cardiomyopathy with Classic Reversal - Amit Harish Baheti; Ravi Kalra; Prashant Bharadwaj; Vaibhav B. Patil (Journal of the Practice of Cardiovascular Sciences)
Takotsubo cardiomyopathy (TCMP) is a form of transient left ventricular (LV) dysfunction which is almost completely reversible. Among the wide range of etiological factors, thyroid hormone dysfunction is considered a rare but potentially treatable cause of TCMP. Other than LV dysfunction patients can present with mechanical as well as electrical complications. LV thrombus is one of the dreadful mechanical complications predisposing to systemic thromboembolic events. QT prolongation though rare can be seen in patients with TCMP either because of the catecholamine excess or the underlying etiology. We present a rare case of a 63-year-old female presenting with acute decompensated heart failure with the presentation of acute coronary syndrome, LV thrombus, and QT prolongation eventually turning to be a case of TCMP with newly detected hypothyroidism and reversal of LV dysfunction, resolution of LV thrombus, and normalization of QT interval within 4 days of treatment.